OVERPRICING PADA PERUSAHAAN NONKEUANGAN DI BURSA EFEK INDONESIA - Pranyoto, Edi (Fakultas Ekonomi Universitas Islam 45, 2019)
There are 213 non-financial companies conduct IPOs from 2010 to 2018, and 23 companies experience Overpricing. This study examined the effect of market conditions, financial leverage, profitability and allocation of IPO to overpricing in non-financial companies. The population of the study used non-financial companies for 8 years amounted to 213 companies with sample selection using purposive sampling method and selected as many as 20 companies. The analysis technique used multiple linear regression. The results showed that market conditions, financial leverage and allocation of IPO funds did not affect overpricing, while profitability variables affected overpricing. This means that the higher the profitability of the company shows the high ability of the company to generate profits so that investors can see it as a profitable company. This can reduce the uncertainty of an IPO in determining a fair stock price to reduce the level of overpricing.